Side-Polished DBR Fiber Laser with Enhanced Sensitivity for Axial Force and Refractive Index Measurement - Xinfeng Yang; Sankhyabrata Bandyopadhyay; Li-Yang Shao; Dongrui Xiao; Guoqiang Gu; Zhangqi Song (IEEE Photonics Journal, 2019)
A highly sensitive optical fiber sensor for the measurement of axial force and refractive index (RI) is presented. The optical sensor consists of a distributed Bragg reflector (DBR) based fiber laser, the laser cavity of the DBR is polished to D-shape by the wheel fiber polishing system. Birefringence has been introduced with side polishing of the fiber, and then, it is utilized for sensing applications. The working principle of the device is based on the principle of the change in beat frequency of the two orthogonal polarization modes of the DBR fiber laser with external perturbations. In this work, it has been shown that the dual polarization beat frequency can be used for RI-based measurement applications along with the measurement of the axial force. The sensitivity of the DBR fiber laser sensor with change in axial force is enhanced significantly with side polishing. Such a device is robust, simple in fabrication and most importantly low-cost interrogation techniques can be used for the detection purpose. A resolution of 5.6014 × 10–8 N has been achieved in case of recognition of axial force and 1.9259 × 10–5 RIU is the observable detection limit for the RI based measurement.